Types and Abundance of Beach Waste in the Coastal Area of Kampung Beran Tanjung Harapan, Meranti Islands District - Exaudi, Bonita Tiolina; Amin, Bintal; Nedi, Syahril (Jurnal Natur Indonesia, 2025)
This research was carried out in June 2023; the research location was on the coast of Kampung Beran, Tanjung Harapan, Meranti Islands Regency. This research aims to determine the type and abundance of beach litter, analyze the differences in the type and abundance of beach waste between stations, and analyze the type and abundance of beach litter between sampling times. Beach litter data collection was taken at three stations, with each station 25m in distance. Each station has three transect lines with nine plots or quadrants measuring 5×5 m2 with a distance between plots of 5m. Sampling was conducted during low tide and on weekdays (Tuesday, Wednesday) and weekends (Saturday, Sunday). Based on the research results, five types of beach litter were found, namely plastic (40%), iron/metal materials (5%), broken glass/ceramic (31%), rubber (3%), wood (11%), and others (10%). The highest abundance of waste occurred on weekdays (10,59 units/m2), and the lowest waste occurred on weekends (7,97 units/m2). ANOVA analysis and independent sample test show that the abundance of beach litter waste between stations and between sampling times did not have significant differences (P > 0.05).